The Effect of MBKM Programme on Career Maturity of Prospective Early Childhood Teacher Students - Fatoni Achmad; Yulia Novita Sari; Kartini Udin; Aulia Miskiran (G-Couns: Jurnal Bimbingan dan Konseling, 2026)
The objective of this study is to analyze the influence of the Merdeka Belajar Kampus Merdeka (MBKM) Program on the career maturity of undergraduate students preparing to become Early Childhood Education (PAUD) teachers at Khairun University. This study employs a quantitative research design using a correlational survey method. The sample consists of 33 students who have participated in the MBKM program. Data were collected through a questionnaire, with validity tested using Pearson correlation and reliability assessed through Cronbach’s Alpha. The results of the hypothesis test showed a p-value of 0.029 < 0.05 and a t-value of 2.292 > the t-table value of 1.696, indicating that the alternative hypothesis is accepted. This means that the MBKM program has a positive effect on students’ career maturity. In addition, the Pearson correlation test yielded a significance value of 0.014 < 0.05 and a correlation coefficient of 0.381, indicating a significant positive relationship of low strength. These findings suggest that while the MBKM program contributes to enhancing career maturity, additional support from other factors is needed to achieve more optimal outcomes. Keywords: career maturity, merdeka belajar kampus, PAUD students